Najib Razak’s political storytelling on Instagram: the fall of a government and the rise of an opposition leader? - Mohamed, Shafizan (Taylor's University, 2019)
This study explores the dynamics of visual imageries on political communication focusing especially on the political storytelling of Najib Razak. Najib Razak is a contested figure in Malaysian politics. He was Malaysia’s 6th Prime Minister and the man responsible for the fall of a 60-year-old government. His dynamic political life offers an interesting case for this study. Image type analysis was carried out on 94 Instagram postings shared by Najib from March 2018 to January 2019. The results showed that Najib actively used Instagram to author his own stories by switching between narratives that were personal and political. These narratives depicted Najib as a resilient politician and a proletarian leader, an image he used to promote his political comeback. Instagram affords politicians a platform to engage in populist politics that celebrates the individual lives of politicians over strict political actions. However, this study argues that while populist politics may take the attention away from ideological issues that guide a politician’s actions and decisions, it still needs scholarly recognition as Instagram and other social media forms are now an inevitable part of political communication. Thus this analysis offers a crucial look at the mediatisation and personalisation of politics and contributes to the academic literature on social media, storytelling, as well as political communication in Malaysia.